Peran Citra Merek Memediasi Pengaruh Kualitas Produk terhadap Keputusan Pembelian Milo Activ-Go UHT - Nurul Anisa; Ni Luh Wayan Sayang Telagawathi (Jurnal Manajemen Perhotelan dan Pariwisata, 2022)
This research aims to test the influence of product quality and brand image on Milo Activ-Go UHT purchasing decision at PT Graha Artha Persada. This study is a causal quantitative study conducted by 80 respondents with purposive sampling techniques. The subject of this study was consumers who bought Milo Activ-Go UHT at least twice at PT Graha Artha Persada. The object of this study focuses on product quality variables, brand image, and purchasing decisions. The data was obtained by questionnaire, and analyzed with path analysis. The results showed that (1) Product quality had a positive and significant effect on purchasing decisions. (2) Brand image has a positive and significant effect on purchasing decisions. (3) Product quality has a positive and significant effect on brand image. (4) The quality of the product has a positive and significant effect on the purchase decision of Milo Activ-Go UHT at PT Graha Artha Persada through brand image.